Long-term monitoring and modeling of PAHs in capped sediments at the Grand Calumet River. (1st July 2023) - Garza-Rubalcava, Uriel; Smith, Alex V.; Thomas, Courtney; Mills, Marc A.; Jackson, W. Andrew; Reible, Danny D.
Abstract: The assessment of a cap for remediation of sediments requires long-term monitoring because of the slow migration of contaminants in porous media. In this study, coring and passive sampling tools were used to assess the transport and degradation of polycyclic aromatic hydrocarbons (PAHs) in an amended cap (sand + Organoclay® PM-199) in the Grand Calumet River (Indiana, USA) during four sampling events from 2012 to 2019. Measurements of three PAHs (phenanthrene (Phe), pyrene (Pyr) and benzo[a]pyrene (BaP), representing low, medium, and high molecular weight compounds, respectively) showed a difference of at least two orders of magnitude between bulk concentrations in the native sediments and the remediation cap. Averages of pore water measurements also showed lower levels in the cap respective to the native sediments by a factor of at least 7 for Phe and 3 for Pyr. In addition, between the baseline (BL), which corresponds to observations from 2012 to 2014, and the measurements in 2019, there was a decrease in depth-averaged pore water concentrations of Phe ( C 2019 / C B L = 0.20 − 0.07 + 0.12 in sediments and 0.27 − 0.10 + 0.15 in cap) and Pyr ( C 2019 / C B L = 0.47 − 0.12 + 0.16 in sediments and 0.71 − 0.20 + 0.28 in the cap). In the case of BaP in pore water, no change was observed in native sediments ( C 2019 / C B L = 1.0 − 0.24 + 0.32 ) and there was an increase in the cap ( C 2019 / C B L = 2.0 − 0.54 + 0.72 ). Inorganic anions and estimates of pore water velocity along with measurements of PAHs were used to model the fate and transport of contaminants. The modeling suggested that degradation of Phe ( t 1 / 2 = 1.12 − 0.11 + 0.16 years) and Pyr ( t 1 / 2 = 5.34 − 1.8 + 5.3 years) in the cap is faster than migration, thus the cap is expected to be protective of the sediment-water interface indefinitely for these constituents. No degradation was noted in BaP and the contaminant is expected to reach equilibrium in the capping layer over approximately 100 years if there exists sufficient mass of BaP in the sediments and there is no deposition of clean sediment at the surface. Graphical abstract: Image 1 Highlights: Remediation cap effectively isolates contaminated solids from surface water Passive sampling measurements are statistically consistent over multiple years Passive sampling of conservative tracers can aid in conceptual model development Observations indicate larger attenuation rates for low molecular weight compounds